Research Progress of in the Treatment of Gastrointestinal Cancer - Lankang Wang MD; Baoyi Ni MD; Jia Wang BMed; Jilai Zhou BMed; Junyi Wang BMed; Jiakang Jiang MD; Yutong Sui MD; Yaoyao Tian MD; Feng Gao BMed; Yufeng Lyu BMed (Integrative Cancer Therapies)
Gastrointestinal (GI) cancer stands as one of the most prevalent forms of cancer globally, presenting a substantial medical and economic burden on cancer treatment. Despite advancements in therapies, it continues to exhibit the second highest mortality rate, primarily attributed to drug resistance and post-treatment side effects. There is an urgent need for novel therapeutic approaches to tackle this persistent challenge. Scutellaria baicalensis , widely used in Traditional Chinese Medicine (TCM), holds a profound pharmaceutical legacy. Modern pharmacological studies have unveiled its anticancer, antioxidant, and immune-enhancing properties. S. baicalensis contains hundreds of active ingredients, with flavonoids, polysaccharides, phenylethanoid glycosides, terpenoids, and sterols being the principal components. These constituents contribute to the treatment of GI cancer by inducing apoptosis in tumor cells, arresting the cell cycle, inhibiting tumor proliferation and metastasis, regulating the tumor microenvironment, modulating epigenetics, and reversing drug resistance. Furthermore, the utilization of modern drug delivery technologies can enhance the bioavailability and therapeutic efficacy of TCM. The treatment of GI cancer with S. baicalensis is characterized by its multi-component, multi-target, and multi-pathway advantages, and S. baicalensis has a broad prospect of becoming a clinical adjuvant or even the main therapy for GI cancer.